(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the ways of developing the professional competence of pedagogues based on digital technologies, increasing the professional competence of pedagogues in international scientific research centers, ensuring their professional pedagogical activities, achieving the effectiveness of the pedagogical process, ensuring the quality and efficiency of education, digital technologies in this process rational use of its capabilities is analyzed.